2022
DOI: 10.3390/ijms231911367
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Consideration in the Interactions between Blood Proteins and Layered Inorganic Materials

Abstract: Interactions between layered double hydroxide (LDH) nanomaterials and plasma proteins according to their particle size and surface charge were evaluated. The LDHs with different particle size (150, 350 and 2000 nm) were prepared by adjusting hydrothermal treatment and urea hydrolysis and subsequent organic coating with citrate, malite and serite was applied to control the surface charge (ζ-potential: −15, 6 and 36 mV). Adsorption isotherms and Stern–Volmer plots for fluorescence quenching indicated that the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Despite the growing interest in LDH as a DDS, there has been only limited information on the hematocompatibility of LDH. We recently reported that LDH itself demonstrated negligible blood cell damage regardless of the particle size surface charge [18] and that LDH did not seriously denature the plasma proteins [11,19]. Other research also reported that surface modification of LDH with polysulfobetaine had excellent blood compatibility [20,21].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the growing interest in LDH as a DDS, there has been only limited information on the hematocompatibility of LDH. We recently reported that LDH itself demonstrated negligible blood cell damage regardless of the particle size surface charge [18] and that LDH did not seriously denature the plasma proteins [11,19]. Other research also reported that surface modification of LDH with polysulfobetaine had excellent blood compatibility [20,21].…”
Section: Introductionmentioning
confidence: 98%
“…Landgraf et al presented that the gold nanoparticleincorporated Fe 3 O 4 with protein corona had enhanced biocompatibility in mouse systems compared with corona-free ones [30]. Meanwhile, we previously reported that LDH nanomaterials were fairly inert to red blood cells (RBCs) regardless of the size and surface charge [18], and that LDH could interact with proteins to different degrees depending on the size and surface charge [19]. The drug-incorporated LDH, of which the surface might be partially covered by the drug, would undergo different blood interactions [11].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the surface control of an individual particle composing bulk material on the nanoscale is also an important issue considering the fabrication and engineering for versatile applications, for example, heterogeneous catalysts [ 13 , 14 ], biological cellular uptake [ 15 , 16 ], and so on. Layered double hydroxide (LDH), one of the layered materials with a chemical formula of [M 2+ 1−x M 3+ x (OH) 2 ] x+ (A n− ) x/n ∙mH 2 O (M 2+ : divalent metal, M 3+ : trivalent metal, A n− : interlayer anion, m: number of interlayer water), is a biologically and environmentally friendly material [ 17 , 18 , 19 , 20 ] and is easily synthesized under mild conditions [ 21 , 22 ] to have high anisotropy [ 23 , 24 ]. LDH is a well-known precursor for mixed metal oxide [ 25 , 26 ], of which the particle morphology is fairly dependent on that of the precursor, LDH [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, nanotechnology-based drug delivery carriers have been intensively studied in order to enhance drug efficacy [ 1 , 2 , 3 ] and to minimize side effects [ 4 , 5 , 6 ]. Various nanomaterials such as liposomes [ 7 ], polymer nanoparticles [ 8 ], 2-dimensional nanomaterials [ 9 , 10 ] and porous nanomaterials [ 2 ] have been under development for these purposes.…”
Section: Introductionmentioning
confidence: 99%